Reasons for Removal of the Moon - Orlov, S. (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2016)
In article the new concept of an explanation of the reason of removal of the Moon from Earth is offered to consideration. It is based on the theory of vortex gravitation, cosmology and a cosmogony. The main reason for this removal is that gravity, the earth's field does not create our planet, and ether vortex The orbital plane of the Moon doesn't coincide with the plane of a gravitational whirlwind that creates reduction of forces of an attraction of the Moon to Earth on some sites of its orbit. Removal of a lunar orbit happens a consequence of it.